Fair rewards for small farmers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Small-scale producers of cash crops traded on the international market, such as coffee, cocoa and tea, have always been farmore vulnerable to falling world prices than big producers. With no power to influence prices their families' livelihoods are...